Dampak Pandemi Covid-19 terhadap Keuangan Perusahaan Penggilingan Padi CV Puspa di Kabupaten Jembrana, Provinsi Bali - DEWI, NI LUH AYUNIA SUNWITHA; SUDARMA, I MADE; RANTAU, I KETUT (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.1, Juli 2022, 2022)
The Impact of The Covid-19 Pandemic on The Finances of The CV Puspa Rice Mill Company, in Jembrana Regency, Bali Province.  The midst of the covid -19 pandemic, many companies experienced changes in the financial problems.  One company that is still operating in the midst of the covid-19 pandemic is CV Puspa, a company engaged in rice milling.  An assessment of the company’s financial performance in the midst of the covid 19 is important to get information about the development of the company’s performance during the pandemic. Financial ratio analysis is used in this study to measure financial company’s performance and see the comparison that occurred in CV Puspa during the pandemic. There are four types of financial ratios analysis are used, namely liquidity ratio, profitability ratio, solvency ratio, and activity ratio.  Based on the results of the analysis, it is known that there is a difference in CV Puspa's financial performance before and during the pandemic.  In addition, CV Puspa's finances are known to be quite good and have experienced several improvements.  Suggestions that the author can give are maintaining liquidity by increasing current assets, maintaining profitability by increasing profits, increasing solvency by making effective use of capital, and maintaining activities by increasing sales.